Obesity prevalence and risks among Chinese adults: findings from China PEACE Million Persons Project, 2014–2018. (25th November 2020) - Mu, L; Liu, J; Zhou, G; Wu, C; Chen, B; Lu, Y; Lu, J; Yan, X; Zhu, Z; Nasir, K; Spatz, E.S; Krumholz, H.M; et al.
Abstract: Background: With demographic and epidemiologic transitions, China has become home to the greatest number of obese individuals in the world. Effective policy intervention requires a contemporary assessment of obesity across broad socio-demographic subgroups. Purpose: We aim to assess the prevalence of overall and abdominal obesity by socio-demographic characteristics and the associations of these characteristics with obesity in China. Methods: Using the data of 2.7-million community-dwelling participants aged 35–75 years in the China PEACE Million Persons Project, a nationwide cross-sectional screening project from 2014 to 2018, we calculated the prevalence of overall and abdominal obesity based on national guideline definitions (body mass index ≥28 kg/m 2, waist circumference ≥85/90 cm for women/men). We examined 12 available socio-demographic variables that are potentially associated with obesity, in addition to self-reported co-morbidities, and quantified the associations of these socio-demographic characteristics with obesity using multivariable mixed models. Results: The prevalence of overall and abdominal obesity were 15.8% and 37.6% in women and 15.0% and 36.3% in men (Figure). Compared to individuals with normal weight, those with overall obesity had a higher prevalence of hypertension, dyslipidemia, and diabetes (in women: by 30.4, 16.1, and 6.0 percent points; in men, by 29.9, 31.2, and 5.8 percent points). A similar pattern was observed with abdominal obesity. In women, those aged 55–64 years constituted the largest age group with overall and abdominal obesity (33.7% and 35.0%), while in men, those aged 45–54 and 55–64 years constituted the largest age group with overall obesity (30.4%) and abdominal obesity (30.5%), respectively. Older women were at substantially higher risk for obesity (e.g., adjusted relative risk [95% CI] of women aged 65–75 vs. 35–44 years: 1.29 [1.27–1.31] for overall obesity and 1.76 [1.74–1.77] for abdominal obesity) while older men were not. Higher education was associated with lower risk in women (e.g., those with college or university education vs. less than primary school: 0.47 [0.46–0.48] for overall obesity and 0.61 [0.60–0.62] for abdominal obesity) but higher risk in men (1.07 [1.05–1.10] and 1.17 [1.16–1.19]). In both women and men, current smoking was associated with lower risk for obesity, and current drinking was associated with higher risk, but the magnitude of associations was smaller in women than men. Conclusions: In China, over one in seven individuals meet criteria for overall obesity, and one in three for abdominal obesity. Wide variation exists across socio-demographic subgroups. The associations of age and education with obesity are significant and differ by sex. Understanding obesity in contemporary China has broad domestic policy implications and provides a valuable international reference. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): The National Key Research and Development Program from the Ministry of Science and Technology of China, the CAMS Innovation Fund for Medical Science